The influence of viral, bacterial and parasitic infections on the development of neoplasia - Markowska, Anna; Lubin, Jolanta; Jaszczyńska-Nowinka, Karolina; Pawałowska, Monika; Mądry, Radosław (Contemporary Oncology/Współczesna Onkologia, 2011)
A relationship exists between certain protracted viral, bacterial and parasitic infections on one hand and development of tumours on the other. A relationship was proven between persistent infection with highly oncogenic types of human papilloma virus (HPV) and the development of precancerous lesions and uterine cervical cancer, a significant proportion of cancers of the anus, penis, vulva and vagina, and a lower proportion of cancers of the oral cavity and the larynx (infection with low-oncogenic types of the virus). It is estimated that around 54% of primary hepatic carcinomas worldwide (hepatocellular carcinoma – HCC) are directly linked to persistent infection with hepatitis type B virus (HBV) and 31% of the cancers result from persistent infection with hepatitis type C virus (HCV). Human immunodeficiency virus (HIV) induces increased morbidity due to certain malignant tumours. The index diseases for the acquired immune deficiency syndrome include Kaposi sarcoma, non-granulomatous lymphomas, primary cerebral lymphoma and carcinoma of the uterine cervix. Epstein-Barr virus (EBV), also known as human herpes virus (4-HH-4), induces Burkitt's lymphoma, but its DNA was also detected also in malignant granulomatosis and in tumours of nasopharynx. Human T-lymphotropic virus (HTLV), particularly in certain regions of the globe, is linked to development of the T cell leukaemia. Among bacteria, relationships with cancer development are manifested by Helicobacter pylori and Chlamydia trachomatis . The first has been classified as a group I carcinogen: chronic infection, with type A of H. pylori in particular, leading to gastric cancer and gastric lymphoma, Chlamydia trachomatis, and its serotypes G, I and D are thought to represent strong co-factors in development of cancer of the uterine cervix. The parasites with proven carcinogenic effects include Schistosoma haematobium, Opisthorchis viverrini and Clonorchis sinensis . The common mechanism involves chronic inflammation which in the case of Schistosoma haematobium results in development of urothelial bladder cancers, particularly in certain endemic regions of the world. The remaining two parasites, particularly in eastern Asia endemically lead to cancers of the biliary ducts.